Linking psychological capital to job embeddedness among nurses: evidence from Egyptian public healthcare setting - Ayman Mohamed El-Ashry; Mahmoud Abdelwahab Khedr; Mona Metwally El-Sayed; Islam Sameh Abdelhay; Mennat-Allah G. Abou Zeid; Bashair Mohamed Elsayed Abdo (BMC Nursing)
Abstract Background Psychological capital, encompassing hope, self-efficacy, resilience, and optimism, is increasingly recognized as a critical resource in enhancing workplace engagement and retention. In high-stress professions such as nursing, psychological capital may serve as a buffer against job demands. However, limited research exists in Egypt exploring how psychological capital influences job embeddedness, a construct reflecting an employee’s attachment to their job and organization. Objective This study aimed to examine the relationship between psychological capital and job embeddedness among nurses working in governmental hospitals in Egypt. Design A cross-sectional, descriptive correlational design was employed, adhering to the STROBE guidelines. Methods Data were collected from 431 registered nurses working across two public hospitals over three months. Standardized tools were used, including the 24-item Psychological Capital Questionnaire and the Global Job Embeddedness Scale. Results Psychological capital showed a significant positive correlation with job embeddedness (r = 0.356, p < 0.001). Regression analysis confirmed PsyCap as a significant predictor of JE (B = 0.317, p < 0.001), accounting for 19.8% of the variance (R² = 0.198). Among PsyCap dimensions, optimism had the strongest individual correlation with JE (r = 0.406, p < 0.001). Conversely, patient load per shift was negatively associated with JE (B = − 0.269, p < 0.001). Conclusion Psychological capital is a significant linked to job embeddedness among Egyptian nurses. Nurses with higher psychological capital levels are more likely to feel anchored in their roles, whereas high patient loads erode this attachment. Nursing implications Healthcare institutions should implement programs to develop nurses’ psychological capital particularly resilience, optimism, and self-efficacy. In parallel, managing nurse workloads is essential to enhancing retention, improving work satisfaction, and ensuring sustained quality care in challenging healthcare environments. Clinical trial number Not applicable.